Molecular responses to freshwater limitation in the mangrove tree Avicennia germinans (Acanthaceae) - Cruz, Mariana Vargas (2020)
Environmental variation along the geographical space can shape populations by natural selection. In the context of global warming and changing precipitation regimes, it is crucial to understand the role of environmental heterogeneity in tropical trees adaptation, given their disproportional contribution to water and carbon biogeochemical cycles. Here, we investigated how heterogeneity in freshwater availability along tropical wetlands has influenced molecular variations of the black mangrove (Avicennia germinans). A total of 57 trees were sampled at seven sites differing markedly in precipitation regime and riverine freshwater inputs. Using 2,297 genome-wide single nucleotide polymorphic markers, we found signatures of natural selection by the association between variations in allele frequencies and environmental variables, including the precipitation of the warmest quarter and the annual precipitation. Additionally, we found candidate loci for selection based on statistical deviations from neutral expectations of interpopulation differentiation. Most candidate loci within transcribed sequences were functionally associated with central aspects of drought tolerance or plant response to drought. Moreover, our results suggest the occurrence of the rapid evolution of a population, probably in response to sudden and persistent limitations in plant access to soil water, following a road construction in 1974. Observations supporting rapid evolution included the reduction in tree size and changes in allele frequencies and in transcript expression associated with increased drought tolerance through the accumulation of osmoprotectants and antioxidants, biosynthesis of cuticles, protection against protein degradation, stomatal closure, photorespiration and photosynthesis. We describe a major role of spatial heterogeneity in freshwater availability in the specialization of this typically tropical tree.